Constraints and opportunities on okra (Abelmoschus esculentus) production in Ethiopia: a review - Massrie, Kelemu Dessie (Frontiers in Sustainable Food Systems, 2025)
Okra (Abelmoschus esculentus) is an important vegetable in Ethiopia due to its nutritional value and culinary uses. However, its production is hindered by several challenges. Key issues include diseases like powdery mildew, fusarium wilt, and viral infections, which significantly reduce yields, and pests such as aphids, whiteflies, and fruit borers that further damage crops. The scarcity of improved okra varieties and insufficient drought management exacerbate these challenges. Farmers' perceptions of okra as a low-value crop affect investment and cultivation practices. Additionally, drought, compounded by poor irrigation infrastructure, poses a severe threat to okra production. Despite these challenges, Ethiopia's diverse agro-climatic conditions and fertile soils in regions like Amhara and Oromia offer favorable environments for cultivating okra, with potential yields reaching up to 20 tons per hectare under optimal management. To overcome these constraints, it is essential to improve disease and pest management, develop and distribute drought-resistant varieties, and educate farmers on better practices. Changing perceptions through awareness and community engagement, coupled with supportive government policies, are crucial for enhancing okra production, thereby improving food security and economic stability for Ethiopian farmers in the future.